2022
DOI: 10.1177/02692163221090385
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study with people with young-onset dementia and their family caregivers on advance care planning: A holistic, flexible, and relational approach is recommended

Abstract: Background: Broad consensus exists on the relevance of advance care planning in dementia. Although people with young-onset dementia and their family are hypothesized to have distinct needs and preferences in this area, they are hardly ever included in studies. Aim: We aim to explore the experiences with and views on advance care planning of people with young-onset dementia and their family caregivers. Design: A qualitative study was conducted, analyzing semi-structured interviews through the method of constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 47 publications
3
21
0
Order By: Relevance
“…The need expressed by professionals to have highly involved caregivers contrasts with the testimonies of caregivers who often feel overloaded and burned by the intensity of care they must provide, often 24 h a day, in patients with a high dependence and burden of symptoms. Responses from health professionals consistently lead to the consideration of shifting palliative care systems towards a holistic and anticipatory planning approach, this is consistent with recent studies with other patient profiles, people with dementia [ 21 ] or heart failure [ 22 ].…”
Section: Discussionsupporting
confidence: 81%
“…The need expressed by professionals to have highly involved caregivers contrasts with the testimonies of caregivers who often feel overloaded and burned by the intensity of care they must provide, often 24 h a day, in patients with a high dependence and burden of symptoms. Responses from health professionals consistently lead to the consideration of shifting palliative care systems towards a holistic and anticipatory planning approach, this is consistent with recent studies with other patient profiles, people with dementia [ 21 ] or heart failure [ 22 ].…”
Section: Discussionsupporting
confidence: 81%
“…In the current study, ACP was considered by physicians to be a means or an opportunity for people with dementia of fulfilling a caretaking role toward their family. It has been previously stated by patients and caregivers that if people with dementia undertake ACP, one of their main purposes is to take care of their loved-ones ( Van Rickstal et al, 2022 ). The relational, as opposed to purely individual, nature of ACP appears evident from the viewpoint of all parties involved.…”
Section: Discussionmentioning
confidence: 99%
“…As such, particularly in the context of dementia, a family-rather than a solely patient-centered approached to ACP 10.3389/fnagi.2023.1130642 could be desirable. As physicians also expressed that their wish to safeguard patients' emotional wellbeing shapes their own behavior in terms of ACP, the previous idea of a mutual protective role between people with dementia and their family caregiver (Van Rickstal et al, 2022) could be extended from a dyad to a protective triad which also includes the professional caregiver.…”
Section: Interpretation Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study found that women who were caregivers reported more stress and greater mental and physical consequences compared to caregivers who were men [72]. People with YOD and their caregivers often took a narrow view on advanced care planning, in that they perceived this as solely as ''end-of life'' issues which they would face when end of life came, rather than an ongoing open discussion about the preferences of the types of care the individuals with dementia would choose [73].…”
Section: Psychosocialmentioning
confidence: 99%